Effects of Wood Content and Modification on Properties of Wood Flour/Polybutylene Adipate Terephthalate Biocomposites - Wangwang Yu; Rui Qiu; Mengya Li; Wen Lei (Molecules, 2023)
Biodegradable polymers have recently become attractive and have been increasingly used as matrix materials to replace fossil plastics due to concerns about the environmental issue. However, their application areas are limited due to their high costs and natural properties. In this study, we fabricated ecofriendly and economical polybutylene adipate terephthalate (PBAT) composites loaded with various concentrations of wood flour (WF) to investigate the effects on the PBAT and WF interfaces as well as the physical properties of the WF/PBAT biocomposites. Then, WF was acetylated with acetic anhydride, and the effect of WF acetylation on the mechanical and thermal properties of the biocomposites were investigated. The results showed that the tensile strength, tensile modulus, flexural strength and flexural modulus increased with WF loading in the composites, and acetylation could not only further increase these properties, but also increase the impact strength and elongation at break. The incorporation of WF would weaken the thermal stability of PBAT, but the thermal stability of the biocomposite could be improved after WF acetylation. The cold crystallization temperature and hydrophobicity of the WF/PBAT samples would be increased with the increasing load of the WF, while the melting enthalpy and the crystallinity of the samples reduced gradually. A morphological analysis of the modified composites revealed that the matrix exhibited greater interfacial interactions with the WF compared to the WF/PBAT. Considering the much lower cost of WF compared to PBAT, the improved properties of WF/PBAT biocomposites will make it economically competitive with other commercial polymers, and these biocomposites should have much wider application areas.